2020
DOI: 10.1542/peds.2020-1056
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of the 2019 Novel Coronavirus (SARS-CoV-2) in 3 Febrile Infants in New York

Abstract: We describe 3 febrile infants <2 months of age admitted to a large tertiary care children’s hospital in New York and subsequently found to be infected with severe acute respiratory syndrome coronavirus 2. All 3 patients presented with fever, feeding difficulty, lymphopenia, and thrombocytosis on laboratory evaluation. Two of the 3 patients were found to have neutropenia, and 2 had known exposures to sick contacts. In this case series, we describe 3 of the youngest patients to be reported with severe acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…6 Since then, a number of case reports and small series describing infants less than 2 months of age have been published, most reporting mild disease, with many infants coming to medical attention due to fever, lethargy and poor feeding, but without respiratory manifestations as seen in adult patients. 7,8,9,10,11,12,13 The largest case series to date describes 18 infants younger than 90 days of age who tested positive for SARS-CoV-2, 14 of whom were febrile. 9 The objective of this study was to compare the clinical and demographic characteristics and hospital course of febrile infants who presented to Cohen Children's Medical Center (CCMC) during March and April of 2020, the time period of peak COVID-19 incidence in our region, to febrile infants treated in CCMC during March and April of previous years.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Since then, a number of case reports and small series describing infants less than 2 months of age have been published, most reporting mild disease, with many infants coming to medical attention due to fever, lethargy and poor feeding, but without respiratory manifestations as seen in adult patients. 7,8,9,10,11,12,13 The largest case series to date describes 18 infants younger than 90 days of age who tested positive for SARS-CoV-2, 14 of whom were febrile. 9 The objective of this study was to compare the clinical and demographic characteristics and hospital course of febrile infants who presented to Cohen Children's Medical Center (CCMC) during March and April of 2020, the time period of peak COVID-19 incidence in our region, to febrile infants treated in CCMC during March and April of previous years.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Febrile infants were also categorized based on their SARS-CoV-2 status: 1 Sixteen of the SARS-CoV-2 infected infants were reported in previous studies. 13,14 This study was approved by the Northwell Health Institutional Review Board.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…10 Last, a case series of infants with MIS-C demonstrated that respiratory manifestations were less prominent, but more vague symptoms, such as irritability and poor feeding, were more frequently encountered when compared with toddlers. 11 All of these cohorts have brought attention to MIS-C, and the call for early recognition and management.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal spread of the disease to neonates from family members or other household contacts occurs and is generally mild. 36 Ongoing/future studies The COVID-19 cohort provides a natural experiment to examine the effects of maternal viral infection while infants were in utero. Such effects may span the lifecycle of these babies; during this time it may be possible to intervene to prevent later life problems.…”
Section: Neonatal Outcomesmentioning
confidence: 99%